Fate of patients with slipped capital femoral epiphysis (SCFE) in later life: risk of obesity, hypothyroidism, and death in 2,564 patients with SCFE compared with 25,638 controls - Hailer, Yasmin D (Acta Orthopaedica, 2020)
Background and purpose — Associations between obesity and slipped capital femoral epiphysis (SCFE) during adolescence are described; however, few studies report on the lifetime risk of obesity in patients with SCFE. In addition, with the obesity epidemic in children and adolescents, an increasing incidence of SCFE might be expected. An association of SCFE with hypothyroidism seems ambiguous, and the association between SCFE and depression and all-cause mortality has not yet been evaluated. This study investigates the associations of SCFE with obesity, hypothyroidism, depression, and mortality, and putative changes in the yearly incidence of SCFE. Patients and methods — 2,564 patients diagnosed with SCFE at age 5–16 diagnosed between 1964 and 2011 were identified in the Swedish Patient Register. These were matched for age, sex, and residency with unexposed control individuals. Cox regression models were fitted to estimate the risk of obesity, hypothyroidism, depression, and death, in exposed compared with unexposed individuals. Results — The risk of obesity (HR 9, 95% CI 7–11) and hypothyroidism (HR 3, CI 2–4) was higher in SCFE patients compared with controls. There was no increase in the risk of developing depression (HR 1, CI 1–1.3) in SCFE patients. In contrast, all-cause mortality was higher in SCFE patients than in controls (HR 2, CI 1–2). The incidence of SCFE did not increase over the past decades. Interpretation — Patients with SCFE have a higher lifetime risk of obesity and hypothyroidism and a higher risk of all-cause mortality compared with individuals without SCFE. These findings highlight the lifetime comorbidity burden of patients who develop SCFE in childhood, and increased surveillance of patients with a history of SCFE may be warranted. The incidence of SCFE did not increase over the last decades despite increasing obesity rates.